Post-Conflict Trauma Recovery Models in the Middle East: A Comparative Analysis - Helsa Nasution; Luthfiah Mawar; M. Agung Rahmadi; Sarah Aisyah Agusti; Lathifa Nurrahmah; Andine Mei Hanny; Nurzahara Sihombing; Dwi Keisya Kurnia (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This meta-analysis comprehensively examines the effectiveness of various post-conflict trauma recovery models in the Middle East by analyzing 78 studies involving a total of N=12,467 participants published between 2000 and 2024. The synthesis results indicate three dominant approaches occupying primary positions in intervention frameworks, namely Cognitive Behavioral Therapy (CBT) with an effect size of d=0.82 (95% CI: 0.76–0.88), Eye Movement Desensitization and Reprocessing (EMDR) with d=0.77 (95% CI: 0.71–0.83), and Narrative Exposure Therapy (NET) with d=0.69 (95% CI: 0.63–0.75). Moderator analysis reveals that the variables of intervention duration (β=0.31, p<0.001) and therapist qualification (β=0.28, p<0.001) play significant roles in determining therapeutic success. CBT demonstrates the highest effectiveness in addressing PTSD (r=0.73, p<0.001), whereas NET proves superior in managing collective trauma (r=0.68, p<0.001). Compared to the findings of Knaevelsrud et al. (2015) and Alzaghoul et al. (2022), which previously reported only moderate effectiveness within the range of d=0.45–0.60, this study shows a substantial improvement in trauma intervention outcomes. Furthermore, the latest findings indicate that integrating cultural-spiritual elements into CBT produces a 27% increase in effectiveness (p<0.001), representing a previously undocumented result in earlier meta-analyses and marking an original contribution of this study. Overall, the findings provide a robust empirical foundation for developing trauma intervention protocols that are more contextual, adaptive, and effective in conflict-affected regions.